Decreasing incidence of upper age restriction enrollment criteria among cancer clinical trials. Issue 3 (April 2020) - Ludmir, Ethan B.; Subbiah, Ishwaria M.; Mainwaring, Walker; Miller, Austin B.; Lin, Timothy A.; Jethanandani, Amit; Espinoza, Andres F.; Mandel, Jacob J.; Fang, Penny; Smith, Benjamin D.; Smith, Grace L.; Pinnix, Chelsea C.; et al.
Abstract: Background: Age disparities among cancer clinical trial participants are pervasive and worsening over time. Identification of factors associated with age disparities is critical to improve enrollment of older patients on trials. The incidence and impact of trial eligibility criteria that exclude patients on the basis of age remains opaque. Methods: ClinicalTrials.gov was queried for completed oncologic randomized controlled trials (RCTs). Phase 3 RCTs assessing a therapeutic intervention among adult cancer patients were included. Trial eligibility criteria were assessed using the ClinicalTrials.gov website as well as trial publications and protocol documentation. Results: Seven hundred and forty-two trials met inclusion criteria, with a total combined enrollment of 449, 720 patients. Upper age restriction enrollment criteria were identified for 10.1% of RCTs; the median age cutoff for restricted trials was 72 years (interquartile range 70–80 years). Linear regression modeling revealed decreasing incidence of age restriction criteria over time, at a rate of −1.1% annually ( p = .03); trials initiating enrollment in 2002–2005, for example, had a 16.1% rate of age-restrictive eligibility criteria, compared with 7.6% for trials initiating enrollment in 2010–2014. Conclusion: Use of eligibility criteria that explicitly exclude patients on the basis of age appears to be decreasing with time. Future efforts should aim to better characterize the relationship between eligibility criteria (such as those that exclude patients on the basis of specific organ function) and their association with age disparities among enrolled patients.